FAKTOR-FAKTOR YANG MEMPENGARUHI PERKEMBANGAN - Oza Salsa; Dwi Nurul Atikah; Linda Yarni (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2024)
Abstract. In normal growth and development, a child will see changes in the size of the body's organs (physical) as the child gets older. Body sizes will increase, both those that are visible such as feet, hands, body height and so on, and those that are not visible such as the heart, lungs, muscles and so on. At the same time, changes are also experienced in the spiritual/mental field, namely increasing the ability to observe, remember, feel, and so on, in line with the physical growth mentioned above, so that a healthy soul will develop in accordance with healthy physical growth as well. The research method is by comparing research methods, processing methods, and the results obtained from each article. The research source comes from articles obtained via the internet in the form of research articles discussing early childhood development. The research results show that the conclusions of the factors that influence the development of western and Islamic psychological perspectives are heredity, environment and God's provisions. In western psychology, emphasis is placed on factors such as heredity and environment in understanding individual development, while in Islamic psychology, the factor of Allah's provisions is also considered very important.